2007
DOI: 10.1590/s1516-14392007000200021
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of commercial ceramic adsorbents and its application on naphthenic acids removal of petroleum distillates

Abstract: The mixture of carboxylic acids present in petroleum oil and directly responsible for its acidity and corrosiveness in liquid phase during the refine process is denominated "naphthenic acids". These acids are also present in distilled fraction of petroleum, causing several problems in final products quality. A possible way to remove the carboxilic acids from petroleum distilled fractions is the adsorption in porous materials. However, the results obtained until now indicate that ion exchange resins would be th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 6 publications
0
6
0
5
Order By: Relevance
“…Para cada espectro, processamentos automatizados foram realizados para designar fórmulas moleculares aos picos com sinal/ruído maior que três (> 3). Os elementos permitidos foram o 12 C, 13 7 (a) Cupom de aço inoxidável 316L; (b) Aquecimento a 180 °C da amostra de óleo com o cupom imerso, por vinte horas; (c) Retirada do cupom; (d) lavagem do cupom, inicialmente com querosene por quatro min, seguido por limpeza com solução de Clark para retirada do produto de corrosão A taxa de corrosão foi calculada pela Equação 4 (Eq. 4), onde mi e mf são as massas iniciais e finais do cupom de aço, respectivamente, t é o tempo de experi e to, ρ é a de sidade da liga etálica (7,86 g cm -3 ) e A é a área exposta do cupom.…”
Section: Espectrometria De Massas De Alta Resolução Por Ft-icr Msunclassified
See 1 more Smart Citation
“…Para cada espectro, processamentos automatizados foram realizados para designar fórmulas moleculares aos picos com sinal/ruído maior que três (> 3). Os elementos permitidos foram o 12 C, 13 7 (a) Cupom de aço inoxidável 316L; (b) Aquecimento a 180 °C da amostra de óleo com o cupom imerso, por vinte horas; (c) Retirada do cupom; (d) lavagem do cupom, inicialmente com querosene por quatro min, seguido por limpeza com solução de Clark para retirada do produto de corrosão A taxa de corrosão foi calculada pela Equação 4 (Eq. 4), onde mi e mf são as massas iniciais e finais do cupom de aço, respectivamente, t é o tempo de experi e to, ρ é a de sidade da liga etálica (7,86 g cm -3 ) e A é a área exposta do cupom.…”
Section: Espectrometria De Massas De Alta Resolução Por Ft-icr Msunclassified
“…6 Esse número é denominado erroneamente por alguns autores como "acidez naftênica", no entanto outros tipos de compostos ácidos além dos ácidos naftênicos contribuem em seu valor, tais como compostos sulfurados, nitrogenados e aromáticos. 6,7 A determinação do TAN tem sido rotineiramente empregada para avaliar a corrosividade do petróleo, considerando-se óleos com número de acidez total maior que 0,5 mg de KOH/g de óleo como sendo potencialmente corrosivos. No entanto, sabese atualmente que este não é um indicador totalmente confiável, já que diferenças significativas na corrosividade de óleos com o mesmo TAN têm sido observadas.…”
Section: Introductionunclassified
“…Acid activation can be affect the physicochemical properties of bentonites and galuconite [37,48]. It was concluded that acid bentonite clays are usually used as oil bleaches, which can favor the adsorption of aromatic color compounds and decrease the adsorption of others compound, mainly naphthenic acids and sulfur compounds [48].…”
Section: Bleachingmentioning
confidence: 99%
“…Additionally, the higher concentrations of NA in crude oils reduce the quality and market at a lower price [53]. Silva et al [48] studied the reducing of corrosion by removing NA from a light petroleum fraction using two commercial adsorbents (clay and activated alumina). Both adsorbents proved a high reduction of the total acid number (TAN) in the residual oils.…”
Section: Corrosion Reductionmentioning
confidence: 99%
See 1 more Smart Citation